2015
DOI: 10.1136/openhrt-2015-000317
|View full text |Cite
|
Sign up to set email alerts
|

Systematic oral hydration with water is similar to parenteral hydration for prevention of contrast-induced nephropathy: an updated meta-analysis of randomised clinical data

Abstract: BackgroundContrast-induced nephropathy (CIN) is the third most common cause of hospital-acquired kidney injury and is related to increased long-term morbidity and mortality. Adequate intravenous (IV) hydration has been demonstrated to lessen its occurrence. Oral (PO) hydration with water is inexpensive and readily available but its role for CIN prevention is yet to be determined.MethodsPubMed, EMBASE and the Cochrane Central register of controlled trials (CENTRAL) databases were searched until April 2015 and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 21 publications
0
18
1
2
Order By: Relevance
“…Nine studies evaluated oral hydration, but were limited by small patient numbers and by the absence of patients with severe renal impairment [ 39 , 41 48 ]. Three meta-analyses concluded that there is no evidence that oral hydration is associated with more risk of PC-AKI compared to IV hydration, but the studies were limited by heterogeneity and lack of hard clinical outcomes [ 49 51 ]. The CMSC does not recommend the use of oral hydration as the sole preventive strategy for PC-AKI, but unrestricted intake of clear oral fluids in addition to IV volume expansion is supported (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies evaluated oral hydration, but were limited by small patient numbers and by the absence of patients with severe renal impairment [ 39 , 41 48 ]. Three meta-analyses concluded that there is no evidence that oral hydration is associated with more risk of PC-AKI compared to IV hydration, but the studies were limited by heterogeneity and lack of hard clinical outcomes [ 49 51 ]. The CMSC does not recommend the use of oral hydration as the sole preventive strategy for PC-AKI, but unrestricted intake of clear oral fluids in addition to IV volume expansion is supported (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, longer intravenous protocols are generally impractical in the outpatient setting. Oral hydration has not been well studied for patients with eGFR less than 30 mL/min/1.73 m 2 or AKI (38,39).…”
Section: Which Patients Should Undergo Prophylaxis To Prevent Aki Primentioning
confidence: 99%
“…Oral hydration has not been well studied for patients with eGFR less than 30 mL/min/1.73 m 2 or AKI. 38 , 39 …”
Section: Key Questions and Joint Nkf-acr Statementsmentioning
confidence: 99%